Infants with Atypical Presentations of Alveolar Capillary Dysplasia with Misalignment of the Pulmonary Veins Who Underwent Bilateral Lung Transplantation - Towe, Christopher T.; White, Frances V.; Grady, R. Mark; Sweet, Stuart C.; Eghtesady, Pirooz; Wegner, Daniel J.; Sen, Partha; Szafranski, Przemyslaw; Stankiewicz, Pawel; Hamvas, Aaron; Cole, F. Sessions; Wambach, Jennifer A. (The Journal of pediatrics, 2018)
To describe disease course, histopathology, and outcomes for infants with atypical presentations of alveolar capillary dysplasia with misalignment of the pulmonary veins (ACDMPV) who underwent bilateral lung transplantation. We reviewed clinical history, diagnostic studies, explant histology, genetic sequence results, and post-transplant course for 6 infants with atypical ACDMPV who underwent bilateral lung transplantation at St. Louis Children's Hospital. We compared their histology with infants with classic ACDMPV and compared their outcomes with infants transplanted for other indications. In contrast with neonates with classic ACDPMV who present with severe hypoxemia and refractory pulmonary hypertension within hours of birth, none of the infants with atypical ACDMPV presented with progressive neonatal respiratory failure. Three infants had mild neonatal respiratory distress and received nasal cannula oxygen. Three other infants had no respiratory symptoms at birth and presented with hypoxemia and pulmonary hypertension at 2-3 months of age. Bilateral lung transplantation was performed at 4-20 months of age. Unlike in classic ACDMPV, histopathologic findings were not distributed uniformly and were not diffuse. Three subjects had apparent nonmosaic genetic defects involving FOXF1. Two infants had extrapulmonary anomalies (posterior urethral valves, inguinal hernia). Three transplanted children are alive at 5-16 years of age, similar to outcomes for infants transplanted for other indications. Lung explants from infants with atypical ACDMPV demonstrated diagnostic but nonuniform histopathologic findings. The 1- and 5-year survival rates for infants with atypical ACDMPV are similar to infants transplanted for other indications. Given the clinical and histopathologic spectra, ACDMPV should be considered in infants with hypoxemia and pulmonary hypertension, even beyond the newborn period.